Clinical case: renal tumor with succinate dehydrogenase deficiency during pregnancy - Fortich, Alejandra; Arrambide, Jose Gustavo; Ruiz, Victor David (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Renal tumors during pregnancy present unique challenges due to the need to balance maternal and fetal health considerations. This case report describes a 31-year-old pregnant woman diagnosed with succinate dehydrogenase (SDH)-deficient renal cell carcinoma (RCC) during the second trimester. The patient presented with lumbar pain and hematuria, leading to the discovery of a left renal mass that was surgically removed via radical nephrectomy, with histopathological analysis confirming SDH-deficient RCC, stage 1. Postoperative care involved anticoagulation therapy, fetal heart rate monitoring and close follow-up. These tumors demand a multidisciplinary approach, with diagnostic tools like ultrasound and MRI to minimize fetal exposure to radiation. SDH-deficient renal tumors, a rare subtype of RCC, requires precise, that requires precise diagnosis due to their association with tumors such as paragangliomas and pheochromocytomas. Treatment strategies, including surgical intervention, are typically tailored to the tumor's characteristics, symptoms, the patient’s wishes and the pregnancy stage, being the second trimester the safest period for surgery. Discussion highlights the importance of individualized care and a collaborative medical approach for optimal outcomes for mother and fetus. Managing renal tumors during pregnancy is complex, requiring careful consideration of maternal and fetal health. A multidisciplinary approach, timely surgical intervention, and individualized treatment plans are essential for optimizing outcomes. Second trimester is often the safest time for surgery, with more aggressive treatments deferred until after delivery, depending on tumor's characteristics and pregnancy stage. This case underscores importance of tailored strategies to ensure the best prognosis for mother and child.